Physiological stress reactivity and recovery: Some laboratory results transfer to daily life - Bamert, Melanie; Inauen, Jennifer (Frontiers in Psychology, 2022)
Stress is a prevalent theme in our daily lives and is related to numerous negative health outcomes. Laboratory research has studied the physiological stress response extensively with objective measures such as heart rate variability (HRV). Recently, the vagal tank theory emerged as a promising approach to predicting adaptive HRV levels around stressful events. This study aimed to investigate whether the predictions of the vagal tank theory about HRV during stress reactivity and recovery translate into naturalistic stressful events in daily life. Sixty-seven students wore an EcgMove 4 sensor for four days to measure HRV. Through a combination of device-based and self-report assessment, HRV data were segmented into before, during, and after stressful events. HRV segments were analyzed with multilevel modelling, accounting for physiological and psychological covariates. HRV before stressful events predicted more adaptive HRV during the event but not HRV recovery afterwards. The results therefore partially support the vagal tank theory’s predictions with data from daily life and allow recommendations for future studies of real-world stress reactivity and recovery. The value of intraindividual variations in HRV as predictors of adaptive stress response is underscored by these findings and could inform future interventions that seek to increase momentary HRV.